A DNA hypermethylation profile reveals new potential biomarkers for the evaluation of prognosis in urothelial bladder cancer. Issue 9 (6th June 2017) - López, Jose I.; Angulo, Javier C.; Martín, Ana; Sánchez‐Chapado, Manuel; González‐Corpas, Ana; Colás, Begoña; Ropero, Santiago
Abstract : DNA hypermethylation has emerged as a molecular biomarker for the evaluation of cancer diagnosis and prognosis. We define a methylation signature of bladder cancer and evaluate whether this profile assesses prognosis of patients. Genome‐wide methylation analysis was performed on 70 tumor and 10 normal bladder samples. Hypermethylation status of 1505 CpGs present in the promoter region of 807 genes was studied. Thirty‐three genes were significantly hypermethylated in ≥10% of the tumors. Three clusters of patients were characterized by their DNA methylation profile, one at higher risk of dead of disease (p = 0.0012). Association between cluster distribution and stage (p = 0.02) or grade (p = 0.02) was demonstrated. Hypermethylation of JAK3 and absence of hypermethylation of EYA4, GAT6, and SOX1 were associated with low‐grade non‐invasive disease. On the other hand, in high‐grade invasive disease hypermethylation of CSPG2, HOXA11, HOXA9, HS3ST2, SOX1, and TWIST1 was associated with muscle invasiveness. A panel of hypermethylated genes including APC, CSPG2, EPHA5, EYA4, HOXA9, IPF1, ISL1, JAK3, PITX2, SOX1, and TWIST1 predicted cancer‐specific survival and SOX1 (HR = 3.46), PITX2 (HR = 4.17), CSPG2 (HR = 5.35), and JAK3 hypermethylation (HR = 0.19) did so independently. Silencing of genes by hypermethylation is a common event in bladder cancer and could be used to develop diagnostic and prognostic markers. Combined hypermethylation of SOX1, PITX2, or CSPG2 signals patients at higher risk of death from bladder cancer.